(untitled) (Journal of Legal Studies, 2020)
Social media provide a more convenient way for daily communication and business transaction, while they are also exploited by potential criminals to perpetrate offenses of different natures. Fraud is one of the most frequently reported offenses, some of which involve the use of WeChat, an application now used by 846 million users worldwide. The article is designed to give a comprehensive statement of features, causes, and types of WeChat fraud currently existing in China. The article also formulates important countermeasures based on academic conclusions, law enforcement opinions as well as written criminal judgments collected from Chinese courts during the research.